Paradigma Integrasi-Interkoneksi Ilmu Agama dan Sains dalam Pemikiran Amin Abdullah: Respons Epistemologis terhadap Isu-Isu Kontemporer - Jannah, Ila; Gunagraha, Shindid; Baidi, Baidi (Balai Diklat Keagamaan Bandung, 2025)
The dichotomy between religious and secular sciences within the Islamic intellectual tradition has led to a stagnation of thought and a weakened ability to respond to contemporary challenges holistically. This study aims to critically examine the integration-interconnection paradigm proposed by Prof. Amin Abdullah as a framework for reconstructing a holistic and contextual Islamic epistemology. Employing a qualitative approach, the research applies library research and content analysis methods on his primary works and related literature. The findings reveal that Amin Abdullah’s paradigm, illustrated through a “spider web” metaphor, emphasizes the interrelatedness between religious, social, and natural sciences. His integration of three epistemological approaches—bayani (textual), burhani (rational), and irfani (spiritual)—provides a dialogical framework for contextual Islamic understanding. The paradigm proves relevant in addressing contemporary issues such as the environmental crisis through multidisciplinary engagement that bridges revelation and empirical science. These findings affirm Amin Abdullah's significant contribution to the development of an inclusive, transformative, and context-responsive Islamic scientific paradigm. Keywords: Knowledge integration; interconnection; Amin Abdullah; Islamic epistemology; religious and scientific knowledge; contemporary issues.